Pattern of infection in children presented with obstructive uropathy: A hospital-based study (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Obstructive uropathy refers to the structural impedance to the flow of urine anywhere along the urinary tract which may result from congenital (anatomic) lesions or can be caused by trauma, neoplasia, calculi, inflatnmatory process or surgical procedure. It is responsible for about 4% of end-stage renal disease. Obstructive uropathy is invariably associated with some co-morbid conditions specially infection.Objecctive: This study was conducted in the department of pediatric nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka, Bangladesh with an objective to identify different pattern of infections in children with obstructive uropathy. Methods: A total of 55 patients of obstructive uropathy were enrolled. Thorough clinical and laboratory evaluation including hematological, biochemical, radiological and radio nucleotide imaging were done along with blood and urine culture. Result: Out of 55 cases, 42.27% of obstructive uropathy was detected between I to 5 years and 89.27% was infected. Among obstructive uropathy cases, majority had posterior urethral valve (PUV) (42.27%). Urinary tract infection was the commonest (60%) type of infections followed by septicemia and respiratory tract infection. Conclusion: Age between 1 to 5 years was the commonest age of children for hospital admission due to obstructive uropathy. Among various manifestations of obstructive uropatby, infections, mostly urinary tract infection was the commonest one.